IMPLEMENTASI PEMBELAJARAN KETERAMPILAN KERAJINAN DENGAN PENDEKATAN PEMBERDAYAAN POTENSI SENI KERAJINAN DAERAH SETEMPAT - Martono Martono (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Craft Skills Learning Through an Approach that Empowers Local Crafts. Craft skills education equips students with practices aiming to make them possess skills through appreciation and creativity activities to produce craft products so that they acquire life skills. Such learning should give them actual learning experiences. It can be carried out by selecting traditional crafts in a particular region and modifying them into modern crafts developed in accordance with the students and societys needs. It can be conducted by means of the OIA (Observe, Imitate, and Add) method to make the students acquire art and craft skills. Craft skills education should employ the contextual approach so that what happens in the learning process at school is identical to what exists in society. An important point that teachers should note is how they can play roles as facilitators and totivators for their students, so that the students competence can develop to the maximum. Keywords: craft learning, art potential learning